The Contribution Of Islamic Religious Education Teacher In Instruding Religious Moderation Attitudes In Students At SMA Sejahtera Prigen Pasuruan - Novianti, Amalia; Jamhuri, M.; Abdullah, Muhammad (Sean Institute, 2023)
Religious moderation as a perspective can be a solution for being open to each other, accepting differences, and maintaining harmony between religious communities. This strengthening of moderation should also be introduced to teenage students because the young souls of teenagers are still unstable and are still in the process of searching for identity so that they are not influenced by radical religious thoughts. With the regulation of the minister of religion that religious teachers are required to be able to strengthen religious moderation among students. So the contribution of Islamic Religious Education teachers at Sejahtera Prigen High School is to instill religious moderation in students through habituation, Islamic Islamic learning and activities that contain religious moderation values. The aims of this study were to: 1. To find out what religious moderation values were instilled by PAI teachers at Sejahtera Prigen Pasuruan High School. 2. Know and describe how the contribution of PAI teachers in instilling an attitude of religious moderation. This study uses a descriptive qualitative approach. The place of research is SMA Sejahtera Prigen Pasuruan which has the right criteria in this study. Collecting data using observation techniques, interviews and documentation. Data analysis was carried out by collecting data, reducing data, presenting and drawing conclusions. Data validity was performed using source, method and time triangulation. The results of this study indicate that: 1. The contribution of PAI teachers in instilling an attitude of religious moderation in SMA Sejahtera Prigen Pasuruan by using ideas and integrated performance through a) learning, b) habituation. The learning used is learning inside and outside the classroom by providing direction, advice, both in the classroom with tolerance material and outside the classroom to provide prohibitions, prevention and sanctions if there are students who do not follow habituation, while the habituation that is carried out is to familiarize students to attend recitation every legi Friday and midday prayer in congregation. 2. The values of religious moderation that are instilled include: a) Tasamuh values (tolerance), b) Musawah (not being discriminatory), c) I'tidal (fair).